The influence of healthcare workers' social support on compliance to medication in multi drug resistant tuberculosis patients at the Regional General Hospital of Dr. Saiful Anwar - Fauzan Adima; Merita Arini (Clinical Epidemiology and Global Health)
Introduction: Tuberculosis (TB) remains a significant public health issue that poses a worldwide challenge. Indonesia has the second highest incidence of tuberculosis (TB) globally, following India. The Ministry of Health of the Republic of Indonesia reported that the estimated incidence of tuberculosis (TB) in Indonesia in 2021 is 969,000 cases, which corresponds to a rate of 354 cases per 100,000 population. Patients with drug-resistant strains of tuberculosis require an extended duration of treatment due to its classification as a chronic illness. Individuals afflicted with tuberculosis (TB) will face a complex array of challenges, including significant levels of stress. In addition to medical intervention, they will also require social assistance from their family and community. According to Johnson and Johnson (2009), health workers can provide role and social support in the form of emotional support, informational support, instrumental support, and assessment and appreciation support. Emotional support refers to provision of emotional encouragement and motivation by health workers. Informational support refers to delivery of information offered by health workers. Instrumental support refers to provision of material assistance to patient that includes transportation, financial, and access support to TBC treatment by health workers. Appreciation support refers to encouragement, praise, or corrective feedback given by health workers to the patient on TB-RO treatment. This study aims to evaluate the influence of healthcare professionals' social support on medication adherence in patients with multi drug resistant tuberculosis (MDR-TB) at the Regional General Hospital of Dr. Saiful Anwar in Malang. Method: This study employed a quantitative research methodology, specifically utilizing a cross-sectional study design. The study included 78 MDR-TB patients currently receiving treatment at RSUD Dr. Saiful Anwar Malang, located in Indonesia's East Java Province. In 2023, the Ministry of Health registered these patients in its Tuberculosis Information System. Results: The most common gender was male at 60.26 %, while the age of most respondents was 45–64 years (43.59 %) and the most education was high school graduation at 38.47 %. The instrumental support variable is the variable that has the most influence on adherence to medication in MDR-TB patients with (Sig. <0.005). Conclusion: Social support from health workers influences adherence to medication in MDR-TB patients.